Performance of non‐traditional hyperglycemia biomarkers by chronic kidney disease status in older adults with diabetes: Results from the Atherosclerosis Risk in Communities Study: 在老年糖尿病患者慢性肾脏疾病状态下非传统高血糖生物标志物的检测效能:来自评估动脉粥样硬化风险社区研究的结果. Issue 4 (21st December 2017) - Jung, Molly; Warren, Bethany; Grams, Morgan; Kwong, Yuenting D.; Shafi, Tariq; Coresh, Josef; Rebholz, Casey M.; Selvin, Elizabeth
Abstract: Background: In people with chronic kidney disease (CKD), HbA1c may be a problematic measure of glycemic control. Glycated albumin and fructosamine have been proposed as better markers of hyperglycemia in CKD. In the present study we investigated associations of HbA1c, glycated albumin, and fructosamine with fasting glucose by CKD categories. Methods: A cross‐sectional analysis was performed of 1665 Atherosclerosis Risk in Communities Study participants with diagnosed diabetes aged ≥65 years. Spearman's rank correlations ( r ) were compared and Deming regression was used to obtain root mean square errors (RMSEs) for the associations across CKD categories defined using estimated glomerular filtration rate and urine albumin:creatinine ratio. Results: Correlations of HbA1c, glycated albumin, and fructosamine with fasting glucose were lowest in people with severe CKD (HbA1c r = 0.52, RMSE = 0.91; glycated albumin r = 0.39, RMSE = 1.89; fructosamine r = 0.41, RMSE = 1.87) and very severe CKD ( r = 0.48 and RMSE = 1.01 for HbA1c; r = 0.36 and RMSE = 2.14 for glycated albumin; r = 0.36 and RMSE = 2.22 for fructosamine). Associations of glycated albumin and fructosamine with HbA1c were relatively similar across CKD categories. Conclusions: In older adults with severe or very severe CKD, HbA1c, glycated albumin, and fructosamine were not highly correlated with fasting glucose. The results suggest there may be no particular advantage of glycated albumin or fructosamine over HbA1c for monitoring glycemic control in CKD. Abstract : Highlights Correlations of glycated albumin, fructosamine, and HbA1c with fasting glucose were all lower at more severe stages of chronic kidney disease stages in older adults with diagnosed diabetes. Our data suggest that the limitations of HbA1c may not be overcome by glycated albumin or fructosamine in the setting of chronic kidney disease.